Computational principles of mobile robotics - Dudek, Gregory, 1958-; Jenkin, Michael, 1959- (Cambridge University Press, 2010)
"This textbook for advanced undergraduates and graduate students emphasizes computation and algorithms for a range of strategies for locomotion, sensing, and reasoning. It concentrates on wheeled and legged mobile robots but also discusses a variety of other propulsion systems. The new edition presents advances in robotics and intelligent machines over the last 10 years, including significant coverage of SLAM (simultaneous localization and mapping) and multi-robot systems. It includes additional mathematical background and an extensive list of sample problems. Various mathematical techniques that were assumed in the first edition are now briefly introduced in appendices at the end of the text to make the book more self-contained"--Resumé vydavatele